2012
DOI: 10.1016/j.jacc.2011.10.877
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related Differences in Clinical Presentation and Outcome of Transcatheter Aortic Valve Implantation for Severe Aortic Stenosis

Abstract: Female sex is associated with better baseline clinical characteristics and improved survival, and is identified as a predictor of midterm survival after TAVI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
110
2
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(124 citation statements)
references
References 15 publications
11
110
2
1
Order By: Relevance
“…Evidence suggests that women have higher pre-operative morbidity and mortality 6 , and lower referral rates 7 . It remains controversial as to whether sex impacts on survival following surgical aortic valve replacement (SAVR) 8 , however, females appear to have improved long term survival following trans-catheter aortic valve replacement (TAVR) [8][9][10] . The longer life expectancy of women or other factors such as LV remodeling and myocardial…”
mentioning
confidence: 99%
“…Evidence suggests that women have higher pre-operative morbidity and mortality 6 , and lower referral rates 7 . It remains controversial as to whether sex impacts on survival following surgical aortic valve replacement (SAVR) 8 , however, females appear to have improved long term survival following trans-catheter aortic valve replacement (TAVR) [8][9][10] . The longer life expectancy of women or other factors such as LV remodeling and myocardial…”
mentioning
confidence: 99%
“…1 Subsequently, multiple investigators have sought to define gender disparities in patients undergoing TAVR (Table I). [2][3][4][5][6][7] Early studies were predominantly single-center, real-world observational studies with relatively small sample sizes; nonetheless, some similar findings emerged. In terms of preoperative characteristics, female patients tended to have smaller body surface areas, smaller aortic annular diameters, and higher left ventricular ejection fractions (LVEF) ( Table II).…”
mentioning
confidence: 85%
“…Procedural differences were most notable for smaller valve sizes in women (Table III). [2][3][4][5][6] In regard to outcomes, the investigators consistently identified a trend toward higher rates of vascular sequelae and bleeding among women who underwent TAVR (Table IV). [2][3][4][5][6] In the largest of these institutional experiences, Humphries and colleagues 5 reported significantly lower mortality rates in women than in men (median follow-up duration, 302 d; estimated 2-yr survival rate, 38.3% vs 27.9%; P=0.007).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Differently from surgical series, women treated by TAVR were approximately 50% (4,6) and seems to have a significant survival advantage compared to the male patients (4,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The overall result of this pooled analysis of studies is shown in Figure 1.…”
mentioning
confidence: 92%